Planning Within Complex Urban Systems - Lai, Shih-Kung (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Imagine living in a city where people could move freely and buildings could be replaced at minimal cost. Reality cannot be further from such. Despite this imperfect world in which we live, urban planning has become integral and critical especially in the face of rapid urbanization in many developing and developed countries. This book introduces the axiomatic/experimental approach to urban planning and addresses the criticism of the lack of a theoretical foundation in urban planning. With the rise of the complexity movement, the book is timely in its depiction of cities as complex systems and explains why planning from within is useful in the face of urban complexity. It also includes policy implications for the Chinese cities in the context of axiomatic/experimental planning theory.
OCLC-licensed vendor bibliographic record.
Keywords: City planning; BUSINESS & ECONOMICS / General